EVALUATION OF TRENDS IN THE NUTRITIONAL STATUS OF STUDENTS AT THANH THUY SECONDARY SCHOOL, HANOI: A THREE-YEAR CONSECUTIVE CROSS-SECTIONAL STUDY - Thi Hong Hanh, Nguyen; Kim Anh, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2024)
This study aims to assess the changes in nutritional status among students aged 11 to 14 at Thanh Thuy Secondary School, Hanoi, over three consecutive years (2021 to 2023). The study involved a total of 606 students in 2021, 638 in 2022, and 694 in 2023. Nutritional status was evaluated based on WHO 2007 guidelines using the WHO AnthroPlus software. Results showed a statistically significant decline in median height from 152 cm in 2021 to 150 cm in 2022 and 2023 (P = 0.036), indicating a decrease in physical stature. The percentage of students with normal nutritional status decreased from 75.4% in 2021 to 69.2% in 2023. Concurrently, moderate thinness increased from 9.6% to 13.3%, and severe thinness rose from 1.5% to 3.2%. Overweight prevalence remained stable at around 11%, while obesity slightly increased from 2.1% to 2.7%. The overall prevalence of malnutrition significantly increased from 24.6% in 2021 to 33% in 2023 (P < 0.05), primarily due to a significant rise in undernutrition, which rose from 11.1% in 2021 to 17.6% in 2023 (P < 0.05). For 11-year-olds, overweight prevalence significantly decreased (P < 0.001), while moderate thinness significantly increased (P = 0.037). Among 12- and 13-year-olds, significant increases in moderate thinness and overweight were observed. These findings underscore the growing issue of the double burden of malnutrition and highlight the need for targeted nutritional interventions among school-aged children.